Digitalization Transformation Adding the "Peek Balance" feature to MBanking Bank Syariah Indonesia - Rista, Uswatun Hasana (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2022)
The existence of globalization helps the spread of technological developments to various countries, so that it becomes unlimited. As a result, technology is becoming more widely known and spreading in human life and it is undeniable that technology is now expanding into various sectors, especially in the banking sector. Digital disruption has changed the way people do business and transact. However, there are still many problems faced in carrying out digital transformation. Among the digital transformations that the company is currently pursuing is realizing BSI's mobile banking into a super app. Of the many advantages offered in the BSI mobile banking application features, there are several drawbacks that make customers not feel satisfied in using this mobile banking application. So reviewing these problems, the author reviews and makes a formula to solve problems that arise from BSI mobile banking users. This study aims to find out how the digitization transformation of additional features will be added in the form of the "Sneak Balance" feature in sharia mbanking (a case study of Indonesian Islamic banks). The type of research used in this research is a literature study, observation and interviews.